Physicochemical Characterization And Antioxidant Potential Of Powder Drink With The Combination Of Dayak Onion (Eleutherine Palmifolia) And Tempe - Tika Pratiwi Khumairoh; Astawan, Made; Prangdimurti, Endang (SEAN Institute, 2024)
Antioxidants play an important role in protecting body health. Sources of natural antioxidants that have not been widely developed are dayak onion and tempe. This research aims to evaluate the antioxidant properties and physicochemical quality characteristics of dayak onion powder dried using the spray dryer (SD) and fluidized bed dryer (FBD) methods and the best combination with tempe powder to produce drink powder. Specifically, this research examines the antioxidant capacity (IC50), total flavonoid content, and color characteristics of dayak onion powder dried using SD and FBD, analyzed with the Independent Sample T-test. The best product of dayak onion powder was dried using FBD instrument and obtained an IC50 antioxidant capacity of 9.16 ± 0.0a ppm, total flavonoids of 6.14 ± 0.04a mgQE/g, whiteness level of 60.6 ± 0 .13b, brightness of 65.3 ±0.16b, a+ of 13.5±0.10a, and b+ of 13.13±0.08b. Dayak onion powder was combined with tempe powder to produce a drink powder, which was evaluated for its physicochemical characteristics using the RAL method and Duncan's test. The best combination of powdered drink products is 40% dayak onion powder + 50% tempe powder, has an IC50 antioxidant capacity (662.95 ± 0.03c ppm) and total flavonoids (4.74 ± 0.04c mgQE/g), with chemical characteristics quality requirements Indonesian National Standard (SNI 7612-2011): protein (32.02±0.35b %w/w), moisture (6.55±0.01b %w/w), ash (1.80±0, 00b %w/w), fat (17.32±0.01b %w/w), aw (0.23±0.01ab) and physical characteristics: viscosity (15.017±0.04b cP), solubility index (9.771 ±0.07b g/ml), bulk density (0.7145±0.00b g/ml) and sedimentation index (9.515±0.18b%).